Pendidikan Pesantren Sebagai Perubahan Sosial Masyarakat Di Desa Koncer Darul Aman Dusun Kampung Baru Tenggarang Bondowoso - Islam, Saiful; Afiyah, Hikmatul (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
ABSTRACT Universally, the existence of pesantren has a dual purpose. First, it maintains Islamic values ​​with an emphasis on the educational aspect. Second, Islamic boarding schools have a role and function in improving public education as an effort to improve the quality of human resources in order to form a society that behaves and understands Islamic values. To obtain valid and correct data, the authors used a qualitative research approach. Meanwhile, the informants were community leaders and pesantren alumni. Researchers make direct observations of the object of research, and the type of research used by researchers is a type of case study research. The results of the research conducted by the researcher were that there were two processes in social change that occurred in the research location, first, community leaders held religious activities aimed at providing an understanding of the community about how to live life according to religious teachings, the second was community leaders implementing the values ​​of pesantren life as a form of practice of what has been taught in activities that have been held. The factors that cause social change in society are caused by the community itself and caused by the occurrence of modernization. As for the impact of social change that occurs is an increase in public awareness of education, especially religious education. Keywords: Islamic Boarding School Education, Community Social Change